(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article analyzes the use of an innovative method as a Linguistic Simulator (listening + reading + speaking) in the study of Russian as a foreign language, especially among students of non-philological universities in online learning. From this point of view, the problem of learning a foreign language based on innovative technologies and methods, which helps self-development, is extremely interesting, and this is relevant during online learning.